Vesicocolic fistula - Rajbhandari, A; Sharma, U; Gyawali, PR; Shrestha, GK; Joshi, BR (Journal of Institute of Medicine Nepal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Vesicoenteric fistulae, also known as enterovesical or intestinovesical fistulae occur between the bowel and the bladder. We report a case of vesicocolic fistula after undergoing TURBT. After confirmation following radiological investigations and cystoscopy the patient underwent repair of the fistula. Keywords:Vesicocolic fistula, enterocutaneous fistula, Gouverneur syndrome Journal of Institute of Medicine, April, 2008; 30:1 61-64 The full text of this paper is available from the Journal of Institute of Medicine website